The determinants of corporate hedging - Lim, Thien Sang; Zatul Karamah A. B. U; Zaiton Osman (Penerbit UMS, 2013)
This study examined the determinants of corporate hedging based on samples taken from non-financial firms on the United Kingdom’s Financial Times Stock Exchange FTSE 250. In this study, derivative usage is used as the proxy for risk management. The research model was estimated using the univariate binomial probit model and the Heckman two-stage regression model. The result indicates that executives with options on company’s shares prefer risk-taking and choose not to hedge. The study also found that corporate hedging is positively related to (1) level of firms’ leverage and (2) proportion of total turnover spent for interest payment. These results suggest that firms that face higher probability of financial distress are using derivatives as risk management tool to stabilised firms’ cash flows. Finally, this study also found that large firms are more likely to use derivatives due to the benefits of economies of scale.